Associations between radiographic characteristics and change in renal function following partial nephrectomy using 24-hour creatinine clearance - Breau, Rodney H. (Canadian Medical Association, 2011)
BACKGROUND: Radiographic characteristics may be associated with the degree of renal function preservation following partial nephrectomy. The purpose of this study was to determine the impact of preoperative radiographic variables on change in renal function using 24-hour urine creatinine clearance (uCrCl). METHODS: Patients with partial nephrectomy performed from November 2003 to 2008 were enrolled in the study. Serum creatinine and 24-hour urine was collected preoperatively and at 3, 6 and 12 months postoperatively. Computed tomography or magnetic resonance imaging was used to determine tumour size, tumour location and renal volume. RESULTS: Of the 36 patients, median age was 62 (range 30–78) and 21 (58%) were male. The mean tumour diameter was 2.8±1.4 cm. Twenty-two (61%) tumours were located at the renal pole and 11 (31%) were endophytic. Overall, mean preoperative uCrCl was 88.8±34.2 mL/min and mean postoperative uCrCl was 82.8±33.6 mL/min (6.8%; p < 0.01). On multivariable analysis, no single characteristic was associated with a clinically prohibitive decrease in renal function (−9.4% if endophitic, p = 0.06; −0.57% per cm diameter, p = 0.73; and −6.9% if located at the renal pole, p = 0.15). The total renal volume was also not significantly associated with renal function change (−1.1% per 100 cc, p = 0.86).